The Connotations and Significance of Cross-Cultural Identity Theory in a Multicultural Context - Cai, Yuqiao (Transactions on Social Science, Education and Humanities Research, 2024)
With the deepening pace of economic globalization, multiculturalism has gradually become a distinctive feature of contemporary society, directly impacting and altering the global cultural landscape. Against this backdrop, the collision and integration of different cultures have become the norm, bringing rich cultural experiences while facing unprecedented challenges. How to achieve mutual cultural identification in a multicultural environment has emerged as a pressing new issue. Research on cross-cultural identity not only focuses on cultural differences and conflicts but also emphasizes finding common ground amidst these differences and seeking reconciliation and coexistence through conflicts. The essence of cross-cultural identity is rich and profound, demanding that we actively seek cultural exchange and integration on the basis of respecting cultural diversity, forming an open, inclusive, and mutually enlightening cultural attitude. Therefore, it is crucial to deeply study and explore the connotations and mechanisms of cross-cultural identity, continuously enhance individual cross-cultural adaptability, and promote intercultural exchange and integration. Only in this way can we achieve mutual cultural identification in a multicultural world and jointly build a harmonious, inclusive, and prosperous world.